Relationship Of Interna Medicine Specialist Doctor Knowledge With Completeness Of Integrated Outstanding Patient's Development Notes At Udayana University Hospital - Budiani, I Dewa Ayu Eka; Purwanti, Ika Setya; Murcittowati, Putu Ayu Sri (Sean Institute, 2022)
Integrated Patient Development Records (CPPT) is the documentation for health workers in reassessing patient's inpatients according to Hospital Accreditation standards. The CPPT is an integrated patient care communication media for health workers to write patient data and treatment plans. The CPPT sheet contains three main components: patient identification, essential records, and patient authentication. The function of collaboration and communication between health professionals will appear in the CPPT form at the hospital. The characteristics of doctors in supporting the completeness of filling out medical records can be seen from specialist doctors' knowledge level. This study aimed to determine the relationship between the knowledge and completeness level of filling out CPPT inpatients by interna specialists at Udayana University Hospital. The research method used in this study is quantitative analysis with a total sample of 85 medical records of interna inpatients and five respondents of interna specialists by using the Probability sampling method, namely random sampling. The results showed that from 5 interna specialist doctors at Udayana University Hospital, it was found that three doctors understood and two doctors did not understand. Of the 85 medical record files studied, the incompleteness of the CPPT form reached 12.96%, while the completeness of the CPPT form reached 87.06%. The results of the Chi-Square test resulted in a p-value of 0.016. This proves that there is a relationship between the level of knowledge and the completeness of the inpatient integrated patient development record form at Udayana University Hospital.